Detection of carbonic anhydrase activity in thermophiles isolated from Malaysian hot spring for biomineralization of CO2 - Humaira, Siddiqui (2022)
Billions of metric tons of CO2 are released annually into the atmosphere, majorly from anthropogenic activities, leading to global warming and climate change. One of the sustainable solutions is carbonic anhydrase enzyme-mediated capture and conversion of CO2 into calcium carbonate for permanent storage or commercial use through biomineralization. Carbonic anhydrase is a metalloenzyme responsible for the reversible hydration of CO2. Recently, carbonic anhydrases have been tirelessly explored and are being unearthed from organisms inhabiting extreme environments. This ubiquitous enzyme isolated from thermophiles is tolerant to extreme temperatures and conditions. This property of CA can be harnessed and adapted for utilization in harsh industrial environments for carbon capture. However, no such study has been conducted to explore the carbonic anhydrases from such an extreme habitat to date in Malaysia. Our study aims to investigate the presence of carbonic anhydrase activity in thermophiles thriving in the Ulu Slim hot spring of Malaysia and its potential to perform CO2 biomineralization. Briefly, two thermophilic isolates named S1 and S2, with a tolerance of 60 °C, were isolated and identified from the Ulu Slim hot spring. These were phylogenetically found to be closely related to Bacillus cereus and Anoxybacillus flavithermus subsp. Yunnanensis, respectively, Further, these isolates successfully displayed carbonic anhydrase (CA) activity which was determined using an electrometric assay called Wilbur- Anderson and in-gel assay known as Protonography. The enzyme activity from isolates S1 and S2 were 35.5 and 21.81 U/mg, respectively. The exhibition of CA activity by the thermophilic isolate S2, in turn, reflected the presence of CA in the species, which had not been reported earlier in the phylogenetically close species Anoxybacillus flavithermus subsp. Yunnanensis, whereas for thermophilic isolate S1, which is phylogenetically close to Bacillus cereus ATCC 14579, the ability to perform biomineralization through partially purified enzyme form was shown for the first time. Additionally, both the isolates demonstrated the ability to enzymatically capture CO2 into a vaterite form of calcium carbonate crystals through precipitation. The morphologies of CaCO3 were observed through Field Emission Scanning Electron Microscopy (FESEM) and Energy Dispersive X-Ray Analysis (EDX). In conclusion, our study explored and confirmed the existence of carbonic anhydrase in an extreme niche of Malaysia with a successful demonstration of its ability to sequester CO2 by the process of biomineralization into calcium carbonate. Moreover, the CA activity from the isolates not only enhanced the hydration but also promoted CaCO3 formation. This study will conceivably open local avenues to explore extreme realms of Malaysia for thermostable enzymes and their usage in enzyme-mediated carbon capture for a permanent carbon dioxide storage solution.